Proceedings of the 1st International Conference on Creativity, Technology, and Sustainability: CCTS 2024, 15–16 May, Jeddah, Saudi Arabia (Proceedings in Technology Transfer, 2025)
This open-access book presents peer-reviewed articles from the 1st International Conference on Creativity, Technology, and Sustainability (CCTS), held on May 15–16, 2024, at Dar Al-Hekma University in Jeddah, Saudi Arabia. It explores the dynamic interplay between technology and sustainability, emphasizing the need for advancements to align with Saudi Arabia's Vision 2030 and the United Nations Sustainable Development Goals (SDGs). The book includes case studies, literature reviews, and scientific works, organized into five main parts: Technology for Innovation and Safety, Sustainable Solutions for Technology and Infrastructure, Transforming Education and Social Impact, Sustainable Environment and Smart Cities, and Technologies for Health, Environment, and Sustainability. Readers will discover how technology fosters innovation, safety, and sustainability across various fields, aligning with specific UN SDGs. Practical applications highlight sustainability awareness and responsible behavior, facilitating knowledge transfer for the public sector, innovative companies, academia, and research centers. Targeting researchers, policymakers, sustainability advocates, and decision-makers committed to achieving the UN's SDGs and Saudi Vision 2030, this book identifies key areas for attention in architecture, design, social and environmental sciences, law, and business. It serves as a valuable guide for professionals in technology-driven sectors like Artificial Intelligence and the Internet of Things, emphasizing technology's vital role in addressing sustainability challenges, enhancing efficiency, promoting environmentally friendly processes, and reducing costs, ultimately improving the quality of life for all.